Perceptions and attitudes on adulthood of selected male and female Filipinos in their twenties - Castillo, Jannica Ruth L. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This study explored the perceptions and attitudes of selected Filipino males and females in their twenties. Using a semi-structured interview tool, the 30 participants, ages 20 to 29, were asked to provide descriptions of who an adult is. They were also asked if at 20-24 years old (younger group), or at 25-29 years old (older group) they already consider themselves as adults, and if given the choice, they would want to go through the stage of adulthood. Results of the study revealed that on the perceptions of adulthood, the three most associated themes on being an adult are: (1) being independent, (2) perceived maturity of personality and behavior, and, (3) based on age, societal norms, biological and legal transitions, with the first two themes consistent with the previous studies done by Arnett (2001). On the perceptions on whether they consider themselves as already adults, 16 out of the 30 participants reported that they are already adults, while only four (4) said that they were not yet adults. Ten (10) participants, mostly belonging to the younger group, reported as seeing themselves as partially adults, and brings the researcher to think about "emerging adulthood" as a sub-level prior to adulthood. For the results on the attitude towards being an adult, majority of the participants (87%) would still want to go through the life stage of adulthood, with the most cited reasons being personal growth and fulfilment. This study recommends further research on adulthood with a wider coverage i.e., single and married, gender groups, rural-urban youth, etc., in order to clearly see how Filipinos view and go through adulthood. It is also recommended to explore the concept of "emerging adulthood" in the local setting to see its implications on the Filipino youth and its differences from Western studies.